Fertilizante organomineral nitrogenado a base de biochar ativado em milho para ensilagem e grão - Silva, Maria Eduarda Abreu da (2024)
To increase productivity and improve the quality of grain production, several treatments are used in the soil, mainly nitrogen fertilization using chemical fertilizers. However, the use of this category of fertilizers can lead to a strenuous release of nitrogen (N), and the processes of nitrate leaching (NO3 - )ammonia volatilization (NH3) and nitrous oxide (N2O) emissions, which result in low N use efficiency, high economic costs and potential for environmental pollution. Biochar, together with mineral fertilizers, becomes an organomineral fertilizer that brings benefits in its use, being a viable alternative to improve the chemical, physical and biological characteristics of the soil; reduce the application doses of exclusively mineral fertilizers, bringing the same productivity results; in addition to GHG mitigation. The objective of this study was to evaluate the effect of activated biochar-based organomineral nitrogen fertilization on chemical and agronomic characteristics and N2O emission in corn for silage and grain. The field experiment was carried out at Embrapa Agrossilvopastoril, while laboratory analyzes were carried out at the Forage Farming Laboratory of the Federal University of Mato Grosso, Campus Sinop-MT. The experimental design used was in randomized blocks, with 4 replications, in a 5x2 factorial scheme, with five doses of N (0; 50; 100; 150 and 200 kg ha-1 ) and two sources (conventional urea and organomineral nitrogen fertilizer with biochar activated - FOM). The agronomic performance of corn was evaluated (plant height, green mass, dry mass, grain productivity), chemical characteristics (buffer capacity - BC, dry matter content - DM, and water soluble carbohydrates - WSC, ash, crude protein - CP and neutral detergent insoluble fiber - NDF). In relation to the soil, the flow and accumulation of N2O, emission factor (EF), NO3 - , ammonium (NH4 + ) and pH were evaluated. The organomineral nitrogen fertilizer with activated biochar showed superior performance in relation to plant height and greater accumulation of dry mass compared to those verified for the chemical fertilizer. Only a dose effect was observed for the CP and NDF variables, where the addition of N increased the CP and NDF content (P > 0,05). In relation to grain productivity, only the dose factor was significant (P > 0,05), with the increase in N doses, an increase in corn productivity was obtained in all treatments, except in the dose of 200 kg ha-1 . The average results of the soil N2O flow, it was found that from the 5th to the 11th day after the fertilization date, peaks of N2O emission occurred, with the most significant peak being on the 7th day after fertilization, mainly in treatments with the highest doses of N. The EF showed a source x dose interaction effect (P = 0,000), the highest EF was measured in our study for the UREA 200 treatment (0,3824%). The soil pH results were between the range of 5,7 and 6,9 with a drop in acidity after the application of fertilizers. In relation to the concentration of NO3 - we observed an increase, after seven days from the fertilization date this occurred in the treatments with the highest doses of N. The organomineral nitrogen fertilizer based on activated biochar promotes superior performance in terms of plant height, dry mass accumulation and CHO content compared to urea; lower emission factor; reduction in N2O emissions and slower release of NO3 - compared to conventional urea. Higher doses of fertilizers contribute to greater N2O emissions.